Kepler's witch : an astronomer's discovery of cosmic order amid religious war, political intrigue, and the heresy trial of his mother /: an astronomer's discovery of cosmic order amid religious war, political intrigue, and the heresy trial of his mother. (2009) - Unknown
No abstract available